2008
DOI: 10.1507/endocrj.k08e-091
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Glucagon-Like Peptide-1 on Hypothalamic Neuropeptide and AMP Activated Kinase Expression in Fasted Rats

Abstract: Abstract. Intracerebroventricular (icv) administration of glucagon-like peptide-1 (GLP-1) inhibits food intake and induces c-fos expression in the hypothalamus. However, the effects of GLP-1 on hypothalamic neuronal activity or neuropeptide mRNA expression are unknown. In this study, we examined the effects of GLP-1 on fasting-induced changes in the expression of hypothalamic orexigenic and anorexigenic neuropeptide. Food intake was significantly inhibited after icv injection of GLP-1 in 48 h fasted rats. Hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 36 publications
3
72
3
Order By: Relevance
“…In that respect, Baumgartner et al (8) observed that the induction of c-fos in the NTS, AP, and CeA was related to the eating inhibitory activity of GLP-1 when it was infused into the hepatic portal vein. Central administration of GLP-1 has also been found to stimulate catabolic neurons in the ARC (43). It is noteworthy that aversive doses of Ex-4 appear to cause a pattern of c-fos induction fairly similar to that seen following nonaversive doses, which let us suppose that the strength of the stimulation (rather than its mere presence) in certain regions might dictate the aversive response.…”
Section: Discussionmentioning
confidence: 92%
“…In that respect, Baumgartner et al (8) observed that the induction of c-fos in the NTS, AP, and CeA was related to the eating inhibitory activity of GLP-1 when it was infused into the hepatic portal vein. Central administration of GLP-1 has also been found to stimulate catabolic neurons in the ARC (43). It is noteworthy that aversive doses of Ex-4 appear to cause a pattern of c-fos induction fairly similar to that seen following nonaversive doses, which let us suppose that the strength of the stimulation (rather than its mere presence) in certain regions might dictate the aversive response.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, a number of these hormones have been shown to influence AMPK activity. In the short term, anorectic agents such as glucose, GLP-1 and oxyntomodulin decrease hypothalamic AMPK activity (Andersson et al 2004, Minokoshi et al 2004, Seo et al 2008, leading to reduction in food intake during satiation, while orexigenic agents such as ghrelin lead to AMPK activation and increased food intake (Andersson et al 2004, Kola et al 2005. In the long term, the circulating anorectic insulin and leptin determine the energy and adiposity profile.…”
Section: Role Of Ampk In the Central Control Of Appetitementioning
confidence: 99%
“…Ghrelin is known to activate neurons in the NTS (Date et al 2006). GLP-1 (7-36) amide, an anorectic hormone, acts both in the hypothalamus and the NTS (Goldstone et al 2000, Seo et al 2008, Hayes et al 2009b). …”
Section: Role Of Ampk In the Central Control Of Appetitementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, icv infusion of GLP-1 in fasted rodents increases the synthesis of anorexigenic peptides (POMC and cocaine-and amphetamine-regulated transcript (CART)) both in arcuate and paraventricular nuclei [94]. In these brain locations, the peptide decreases the synthesis of orexigenic peptides (neuropeptide Y (NPY) and agouti-related peptide (AgRP)).…”
Section: The Gut-to-brain Glp-1-dependent Axismentioning
confidence: 99%